Relationship between plasma xanthine oxidoreductase activity and left ventricular ejection fraction and hypertrophy among cardiac patients. - Yuki Fujimura; Yohei Yamauchi; Takayo Murase; Takashi Nakamura; Shu-Ichi Fujita; Tomohiro Fujisaka; Takahide Ito; Koichi Sohmiya; Masaaki Hoshiga; Nobukazu Ishizaka (PLoS ONE)
Background and purpose Xanthine oxidoreductase (XOR), which catalyzes purine catabolism, has two interconvertible forms, xanthine dehydrogenase and xanthine oxidase, the latter of which produces superoxide during uric acid (UA) synthesis. An association between plasma XOR activity and cardiovascular and renal outcomes has been previously suggested. We investigated the potential association between cardiac parameters and plasma XOR activity among cardiology patients. Methods and results Plasma XOR activity was measured by [13C2,15N2]xanthine coupled with liquid chromatography/triplequadrupole mass spectrometry. Among 270 patients who were not taking UA-lowering drugs, XOR activity was associated with body mass index (BMI), alanine aminotransferase (ALT), HbA1c and renal function. Although XOR activity was not associated with serum UA overall, patients with chronic kidney disease (CKD), those with higher XOR activity had higher serum UA among patients without CKD. Compared with patients with the lowest XOR activity quartile, those with higher three XOR activity quartiles more frequently had left ventricular hypertrophy. In addition, plasma XOR activity showed a U-shaped association with low left ventricular ejection fraction (LVEF) and increased plasma B-type natriuretic peptide (BNP) levels, and these associations were independent of age, gender, BMI, ALT, HbA1C, serum UA, and CKD stages. Conclusions Among cardiac patients, left ventricular hypertrophy, low LVEF, and increased BNP were significantly associated with plasma XOR activity independent of various confounding factors. Whether pharmaceutical modification of plasma XOR activity might inhibit cardiac remodeling and improve cardiovascular outcome should be investigated in future studies.